2013
DOI: 10.1080/10410236.2013.822770
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Cancer Information Environment: The Reciprocal Relationship Between Patient–Clinician Information Engagement and Information Seeking from Nonmedical Sources

Abstract: Prior theory has argued and empirical studies have shown that cancer patients rely on information from their health care providers as well as lay sources to understand and make decisions about their disease. However, research on the dynamic and interdependent nature of cancer patients’ engagement with different information sources is lacking. This study tested the hypotheses that patient-clinician information engagement and information seeking from nonmedical sources influence one another longitudinally among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…For example, 72% of US Internet users and 50.5% of UK breast cancer patients searched the Internet for health information. The initial information found from online non‐medical sources often has an important effect on subsequent patient–clinician information engagement . However, because the type of organised monitoring for rigorous quality control that exists for print resources (such as magazines and journals) does not exist for websites, the reliability of posted information varies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 72% of US Internet users and 50.5% of UK breast cancer patients searched the Internet for health information. The initial information found from online non‐medical sources often has an important effect on subsequent patient–clinician information engagement . However, because the type of organised monitoring for rigorous quality control that exists for print resources (such as magazines and journals) does not exist for websites, the reliability of posted information varies .…”
Section: Introductionmentioning
confidence: 99%
“…The initial information found from online non-medical sources often has an important effect on subsequent patient-clinician information engagement. 4 However, because the type of organised monitoring for rigorous quality control that exists for print resources (such as magazines and journals) does not exist for websites, the reliability of posted information varies. 5,6 For instance, unverified health rumours may be included in health-related search results.…”
Section: Introductionmentioning
confidence: 99%
“…We included the Lerman Cancer Worry scale as a confounder because an earlier analysis showed that worry was a significant predictor of subsequent patient-clinician information engagement; in contrast, the reverse relationship (patient-clinician information engagement or seeking from non-medical sources predicting subsequent worry) was non-significant (41). Because of the presence of gender-specific cancer types, we combined gender and cancer type into a single covariate such that four categories were controlled for in the analysis (female colorectal, male colorectal, breast, and prostate cancers).…”
Section: Methodsmentioning
confidence: 99%
“…Further research should follow to explore how to maintain engagement of patients during AS and to build occasions within AS for taking patients on board. Literature emphasised the role of healthcare professionals for patient engagement (Batalden et al, 2016;Moldovan-Johnson, Tan, & Hornik, 2014;Tan, Bourgoin, Gray, Armstrong, & Hornik, 2011) and, at the same time, their barriers and resistances (Légaré, Ratté, Gravel, & Graham, 2008;Lelorain, Bachelet, Bertin, & Bourgoin, 2017;Moore et al, 2016). Attention should be paid on training healthcare professionals in a new partnership with patients.…”
Section: Engage In the Care Systemmentioning
confidence: 99%